A comparative evaluation of light cure calcium silicate and resin-modified glass ionomer as indirect pulp capping agent in primary molars: A randomized clinical trial - Roshni A Bhatt; Megha C Patel; Rohan Bhatt; Chhaya Patel; Kaushal R Joshi; Disha Makwani (Wolters Kluwer Medknow Publications, 2023)
Background: Minimally invasive techniques should be employed to maintain pulp vitality without affecting physiological tooth resorption for pediatric patients. This study aims to evaluate clinical and radiographic success of light cure calcium silicate and resin-modified glass ionomer (RMGI) as indirect pulp-capping agent in primary molars in children between 5 and 9 years. Materials and Methods: In this randomized clinical trial study, 40 primary molars with the International Caries Detection and Assessment System criteria 4-6 score were divided randomly into two groups after computerized randomization method. After caries excavation by minimally invasive dentistry principle, affected dentin was lined by either light cure calcium silicate (Group I) or RMGI (Group II) liner followed by composite restoration. Clinical success was determined with the absence of symptoms and bitewing radiographs were taken at baseline, 3, and 6 months' interval to measure increase in dentin increment using ImageJ software. Statistical analysis for intergroup comparison was done using Paired t-test, and Independent t-test was used for intragroup comparison. The level of statistical significance was set at P < 0.05. Results: Change in dentin increment seen from baseline to 6 months in Group I was 0.19 mm and in Group II was 0.20 mm (P = 0.924). Intragroup increment was statistically significant during all follow-up intervals for both the groups (Group I - P ≤ 0.001, Group II - P = 0.009). For baseline remaining dentin thickness >1.5 mm, statistically significant increase was observed in the dentin increment at 3 months' interval between both the groups. Conclusion: Both TheraCal LC and Vitrebond show acceptable clinical and radiographic results when used in primary molars as indirect pulp treatment agents. Both the liners are equivalent to each other in terms of feasibility and cost-effectiveness but TheraCal LC can be preferred due to better handling and avoiding the manipulation step thereby reducing treatment time.